Unusual Presentation Of Kawasaki Disease With Gastrointestinal And Renal Manifestations - Lazea C; Man O; Sur LM; Serban R; Lazar C (Dove Medical Press, 2019)
Cecilia Lazea,1,* Oana Man,2,* Lucia Maria Sur,1 Radu Serban,1 Calin Lazar1 1University of Medicine and Pharmacy, Emergency Clinic Hospital for Children, Department Pediatrics I, Cluj-Napoca, Romania; 2Emergency Clinic Hospital for Children, Department Pediatrics I, Cluj-Napoca, Romania*These authors contributed equally to this workCorrespondence: Cecilia LazeaUniversity of Medicine and Pharmacy, Iuliu Hatieganu Cluj-Napoca, Department Pediatrics I, 68, Motilor Street, Cluj-Napoca 400370, RomaniaTel +40744353764Fax +40264402539Email cicilazearo@yahoo.comAbstract: Diagnosis of Kawasaki disease (KD) is based on well-established clinical criteria. In incomplete or atypical KD, the diagnosis is challenging, because of the paucity of clinical signs or because of the presence of clinical manifestations that generally are not seen in KD. We describe the case of a 3-year-old female patient with persistent high fever, vomiting, watery diarrhea, metabolic acidosis and severe hypopotassemia. On the fourth day of fever, bilateral conjunctivitis, mucous and extremity changes were registered. Urine changes as glycosuria and proteinuria were also noticed. Echocardiography revealed ectasia of the left anterior descending coronary artery, and diagnosis of KD was established. The treatment consisted of intravenous immunoglobulin (IVIG) and oral aspirin. Recurrence of disease was recorded on the 23rd day of the disease, with favorable evolution after the second dose of IVIG was infused.Keywords: atypical, incomplete, Kawasaki disease, gastrointestinal, renal